Influence of Water Regulation on Runoff in Dongjiang River Basin - ZHUANG Shengjie; CHENG Zhongli; ZHENG Yafeng; WANG Dagang (Renmin Zhujiang)
To comprehensively analyze the influence of water regulation on the outflow of the three major reservoirs and the flow rates at key sections in the Dongjiang River Basin, this study employs the Mann-Kendall trend test to analyze the changes in the rainfall-runoff trend across the Dongjiang River Basin. Through the utilization of the continuous sliding window method and the multivariate dynamic time warping (MDTW) method, typical low-flow events are identified. Furthermore, similar events within the Dongjiang River Basin are effectively pinpointed. The investigation centers on the outflow processes of the three major reservoirs and the corresponding flow variations at critical sections. The results indicate that since the establishment of the three major reservoirs, there has been no significant alteration in rainfall-runoff patterns during both flood seasons and dry seasons in the Dongjiang River Basin. After water regulation, the compliance rate of dry year flow at the Boluo and Longchuan sections experienced a substantial increase, rising from 42% and 86% to 59% and 98%, respectively, which is significantly higher than that before water regulation. In examining four typical events under similar conditions, the outflow processes of the three major reservoirs demonstrated heightened stability. Notably, the average flow at the Boluo section escalated from 260 to 381 m3/s. This pivotal enhancement underscores the necessity for water regulation, providing a theoretical foundation for its continuation.